Menyelami Potensi Kecerdasan Buatan: Perspektif Mahasiswa Arsitektur dalam Membangun Masa Depan Desain - Sahril Nurfadhilah, Ulfaizah; Haristo Rahman, Muhammad; Saputra, Wahyu (Universitas Medan Area, 2025)
Artificial intelligence has evolved from being a design tool to a system capable of performing design analysis, generating architectural concepts. This study aims to explore students' views on AI that can complement their creativity and contextual sensitivity. Using a survey approach with a descriptive quantitative design, it explores students' perspectives on Artificial Intelligence. The findings show that although AI has significant potential to improve efficiency in the architectural profession, aspects such as creativity, empathy, and cultural sensitivity remain beyond the reach of technology.